NPF as a Moderator of Internal and External Factors on Total Assets: Evidence from Islamic Commercial Banks in Indonesia 2011-2024 - Defrangga Piyu Pramudita; Khusnudin Khusnudin (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study examines the role of Non-Performing Financing (NPF) as a risk-based moderating mechanism in shaping the relationship between internal bank conditions, external macroeconomic factors, and total asset in Indonesian Islamic commercial banks. Drawing on financial intermediation and risk management theory, the study argues that the effectiveness of liquidity, capitalization, and macroeconomic stability in driving asset expansion depends critically on credit risk conditions. Using monthly time-series data from 2011 to 2024 and a causal quantitative framework, the analysis evaluates how key internal factors (Financing to Deposit Ratio and Capital Adequacy Ratio) and an external factor (exchange rate) influence total assets under varying levels of NPF. The results show that while internal and external factors positively contribute to asset growth, NPF significantly weakens the impact of liquidity, capital adequacy, and exchange rate movements on total assets, indicating that rising credit risk constrains the transmission of financial and macroeconomic strengths into balance sheet expansion. Conversely, the moderating role of NPF is not evident in profit-sharing financing. These findings provide novel empirical evidence that credit risk does not merely affect bank performance directly but systematically alters the effectiveness of core total asset drivers in Islamic banking. From a policy perspective, the results underscore that asset growth strategies in Islamic banks must be accompanied by strengthened risk governance and financing quality controls to ensure sustainable expansion, particularly during periods of macroeconomic volatility.